Inovasi Penggunaan Alat Peraga Edukatif dalam Meningkatkan Pemahaman Siswa pada Mata Pelajaran Fiqih Materi Haji - Syaifullah, Dimas Ahmad; AR, Zaini Tamin (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2024)
This study aims to develop and test the effectiveness of a teaching strategy using educational teaching aids on the topic of Hajj rituals in Islamic Religious Education. Employing a qualitative descriptive approach, the research was conducted with seventh-grade students at MTS Al-Azhar Lamongan. Educational teaching aids, such as a miniature Ka'bah and replicas of pilgrimage sites, were utilized to visualize the steps of performing Hajj. The results indicate a significant improvement in students' understanding of Hajj materials, with 93.3% of students reporting increased motivation to learn. Furthermore, this method enhanced student engagement in learning, creating a more interactive and effective classroom environment. This study highlights the importance of innovation in teaching methods to bridge abstract concepts with concrete experiences, particularly in Islamic Religious Education. Recommendations are provided for further development of teaching aids and policy support to facilitate broader implementation.